Penegakan Hukum Terhadap Pendirian Bangunan Dikawasan Daerah Aliran Sungai (Das) (Studi Di Kecamatan Dolopo Kabupaten Madiun Jawa Timur) - Heru Kuswanto; Sigit Sapto Nugroho; Sarbini (Universitas Merdeka Madiun, 2024)
Abstract— The purpose of this study was to determine law enforcement against the construction of buildings in the Watershed area of Dolopo District, Madiun Regency and find out the settlement of the construction of buildings that violate the watershed area. The type of research used is empirical research with a qualitative approach based on primary data, namely observation, interviews and document studies. Secondary data are social facts referenced from books, research results and scientific journals. And analyzed using descriptive research methods, that researchers in analyzing wish to provide an overview or description or subject and research object as the results of the research he did. Based on the results of the research, it shows that law enforcement against the construction of buildings in the watershed area, it is better for the community to obtain permits (IMB) to construct buildings in the river basin and the government is expected to be more intensive in conducting outreach and site surveys in the watershed area to the fullest so that the community is aware and no longer constructing buildings in the watershed area.